2020
DOI: 10.1371/journal.pone.0212530
|View full text |Cite
|
Sign up to set email alerts
|

Long-term historical and projected herbivore population dynamics in Ngorongoro crater, Tanzania

Abstract: The Ngorongoro Crater is an intact caldera with an area of approximately 310 km 2 located within the Ngorongoro Conservation Area (NCA) in northern Tanzania. It is known for the abundance and diversity of its wildlife and is a UNESCO World Heritage Site and an International Biosphere Reserve. Long term records (1963-2012) on herbivore populations, vegetation and rainfall made it possible to analyze historic and project future herbivore population dynamics. NCA was established as a multiple use area in 1959. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…The NCA is inhabited by the Maasai tribe, a semi-nomadic, pastoralist ethnic group traditionally ranging from central Kenya to southern Tanzania (Fratkin, 2001). The Maasai and their livestock resided in the Crater until 1974, when they were evicted and required to live in other parts of the NCA (Moehlman et al, 2020). They were still allowed to enter the Crater to conduct diurnal pastoralism until it was banned at the end of 2016 (Melubo & Lovelock, 2019).…”
Section: Study Area and Populationmentioning
confidence: 99%
“…The NCA is inhabited by the Maasai tribe, a semi-nomadic, pastoralist ethnic group traditionally ranging from central Kenya to southern Tanzania (Fratkin, 2001). The Maasai and their livestock resided in the Crater until 1974, when they were evicted and required to live in other parts of the NCA (Moehlman et al, 2020). They were still allowed to enter the Crater to conduct diurnal pastoralism until it was banned at the end of 2016 (Melubo & Lovelock, 2019).…”
Section: Study Area and Populationmentioning
confidence: 99%
“…Various studies on herbivores analyzed the long-term population trends and assessed the seasonal stability of wild herbivore communities in the Ngorongoro Conservation Area (NCA) [ 30 ]. In addition, some studies found that the exclusion of resident pastoralists and their livestock from the Ngorongoro crater resulted into both increasing and decreasing trends of some ungulate species whereas overall, wildlife biomass remained unchanged [ 31 , 32 ]. However, as humans continue to impact natural habitats and livestock populations still grow within NCA, there is an increasing need to understand how this affects distributions and group sizes of wild herbivores in this Man and Biosphere reserve [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant with these changes, there is mounting evidence to show that populations of some wildlife species (i.e. gazelle species, wildebeest, kongoni ( Alcelaphus buselaphus cokii ), waterbuck ( Kobus ellipsiprymnus ) and eland ( Taurotragus oryx ) have declined in the Ngorongoro caldera (Estes et al., 2006, Moehlman et al, 2020). These species preferred the short grasslands as maintained through prescribed burning.…”
Section: Introductionmentioning
confidence: 99%
“…These species preferred the short grasslands as maintained through prescribed burning. Since the practice of burning was banned from 1975, grasslands supported taller grass stands benefitting Cape buffalo ( Syncerus caffer , Fyumagwa et al., 2007) and elephant populations, while plains zebras have remained stable (Moehlman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation